The Human Factor: Training and Professional Development as a Policy Tool - Lucian CIOLAN; Mihaela STÎNGU; Elena MARIN (Transylvanian Review of Administrative Sciences, 2014)
In this paper, we try to make a case for the risky approach of many decision-makers and pol- icy specialists to overuse authority and regula- tion-based tools, while neglecting the ones more focused on human capacity and persuasion. Especially in fields like education, we consider that the human factor should be at the core of any policy mix, and a tool like training and pro- fessional development should gain a more visible and persistent role in policy interventions. Firstly, we try to analyze the distribution of policy tools on the authority-complexity axes. The value we see in the mapping of policy tools is that it can be used for investigating and positioning the activity of a specific governing body or central gover- nance. Thus, a fundamental question remains as to what really influences the choice of policy tools or instruments, as a basis for better understand- ing the rationales behind a specific policy mix. We argue that policy failure could be ex- plained in many cases by the incapacity to ad- dress in a consistent and professional way the human capacities needed for implementation. Thus, training and professional development are, at least, poorly used from the perspective of the potential they have. As an argument, we tried to look at training and professional development in the specific area of teachers in pre-university education in Romania, situating it in the broader context of European policies in lifelong learning and participation of adults in continuing educa- tion and training, but also in the local policy en- vironment. The results of the research led us to the conclusion that educational policies should be among the first in the broader spectrum of public policies valuing and emphasizing learning, through training and professional development of the stakeholders involved in policy change together with adding more value to the Human Factor in educational policies.